2020
DOI: 10.2340/00015555-3507
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-blind, Placebo-controlled Clinical Study to Investigate the efficacy of Herring Roe Oil for treatment of Psoriasis

Abstract: The effect of herring roe oil capsules was tested in patients with psoriasis. This study demonstrates a positive effect on psoriasis. Disease severity is important when determining the appropriate treatment of psoriasis patients. In recent years, several new drugs have become available for the treatment of severe psoriasis whereas there have been few treatment advances for patients with milder psoriasis. This study demonstrates promise for herring roe oil as a safe treatment option in patients with non-severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“… 35 The daily intake of 10 capsules of herring roe oil in another blinded RCT (64 patients; 26 weeks) resulted in a mean delta PASI of −1.8, versus a mean delta PASI of −0.6 in the placebo group (p=0.045) after 26 weeks. 36 A smaller blinded RCT (n=32) did not find statistical differences in total BSA change at week 12 between patients taking 10 fish oil capsules daily versus a placebo. However, a very subtle, but statistically significant difference in erythema score was found between the groups, in favor of the fish oil group compared to the control group (erythema −1.1 vs - 0.2, resp.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“… 35 The daily intake of 10 capsules of herring roe oil in another blinded RCT (64 patients; 26 weeks) resulted in a mean delta PASI of −1.8, versus a mean delta PASI of −0.6 in the placebo group (p=0.045) after 26 weeks. 36 A smaller blinded RCT (n=32) did not find statistical differences in total BSA change at week 12 between patients taking 10 fish oil capsules daily versus a placebo. However, a very subtle, but statistically significant difference in erythema score was found between the groups, in favor of the fish oil group compared to the control group (erythema −1.1 vs - 0.2, resp.…”
Section: Resultsmentioning
confidence: 92%
“… I: 10 capsules herring roe oil (containing fatty acids EPA and DHA) daily C: Placebo: 10 capsules coconut oil daily Stable topical anti-psoriatic treatments. Tveit et al 36 (2020) X X X 64 26 wks Y N Mean ± SD Δ PASI at wk 26: I −1.8 ± 2.6 C −0.6 ± 1.8 (p=0.045). No differences in PASI50, BSA or PSGA.…”
Section: Resultsmentioning
confidence: 98%
“…In the preceding randomised period (26 weeks), a statistically significant mean reduction in PASI in the HROgroup versus the placebo group was observed [6]. The clinical relevance of the observed mean PASI improvement [11,12] during the randomised period could not be readily concluded.…”
Section: Discussionmentioning
confidence: 89%
“…We explored the efficacy of HRO in a randomised, double blind, placebo controlled clinical study in psoriasis patients with baseline PASI score < 10 [6]. The randomised study period lasted for 26 weeks and all eligible patients were invited to continue a 39-week, open-label, active treatment period.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have consistently revealed their crucial roles in inhibiting chronic diseases, including inflammatory, carcinogenic, adipogenic, diabetogenic, and atherogenic diseases. 8 Moreover, previous studies have also found that supplementation of n3 PUFA (rich in EPA and DHA) improves the condition of psoriasis, 3,[9][10][11][12] but other studies have not found similar results. 13,14 More researches are needed to confirm the relationship between n3 PUFA intakes and psoriasis.…”
Section: Introductionmentioning
confidence: 98%